Nitrogen-Doped Carbon Materials for Persulfate Activation via Electron Transfer Pathways - Jiang, Ziyi (Langmuir : the ACS journal of surfaces and colloids, 2024)
The incorporation of nitrogen into carbon materials is a strategy that effectively boosts their catalytic potency. Herein, a nitrogen-enriched carbon substance, designated as CN0.6, was synthesized from melamine, serving as a precursor. This substance has been established to act as an efficient catalyst devoid of metals for the activation of peroxymonosulfate (PMS). At a temperature of 25 °C, a concentration of 0.05 g/L CN0.6 along with 1 mM PMS suffices to achieve the complete degradation of concentrated tetracycline hydrochloride (TC) in a short period of 4 min. This enhanced catalytic performance is attributed to the optimal level of nitrogen doping, which elevates the pyrrolic nitrogen content and introduces additional defects characterized by an ID/IG ratio of 1.02. These factors collectively augment the adsorptive capacity for PMS and create a greater number of active sites to facilitate its activation. The dominance of a nonradical electron transfer mechanism in the CN0.6/PMS system has been confirmed through a series of analyses, including radical identification, quenching tests, and electrochemical assessments. Employing high-resolution liquid chromatography coupled with tandem mass spectrometry (LC-MS), the investigation identified three potential degradation routes for TC. Furthermore, the intermediates produced are determined to possess reduced toxicity in comparison to TC. The findings of this study offer a approach to the synthesis of highly efficient nitrogen-doped, metal-free catalysts, presenting a promising strategy for the degradation of environmental pollutants